Advancing Arabic Language Learning in the Digital Era: A Multicultural Curriculum Framework - Anggi Nurul Baity; Putri Kholida Faiqoh (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
Developing Arabic language curriculum within multicultural contexts is essential for enhancing educational outcomes in diverse countries like Indonesia. This study uses a literature review to examine how incorporating elements of Arab culture into the curriculum can improve cross-cultural understanding and social cohesion. The research finds that an intercultural approach effectively addresses challenges such as the diverse linguistic and cultural backgrounds of students and the need for relevant teaching materials. Additionally, integrating technology and digital media enriches the learning experience by making it more contextual and inclusive. The study highlights the importance of training educators in intercultural skills and the use of technology to enhance the quality of Arabic language teaching in multicultural settings. Overall, this approach can strengthen cultural integration in the Arabic curriculum and better prepare students for effective communication in a globalized world.